Decoding clinical biomarker space of COVID-19: Exploring matrix factorization-based feature selection methods. (July 2022) - Saberi-Movahed, Farshad; Mohammadifard, Mahyar; Mehrpooya, Adel; Rezaei-Ravari, Mohammad; Berahmand, Kamal; Rostami, Mehrdad; Karami, Saeed; Najafzadeh, Mohammad; Hajinezhad, Davood; Jamshidi, Mina; Abedi, Farshid; Mohammadifard, Mahtab; et al.
Abstract: One of the most critical challenges in managing complex diseases like COVID-19 is to establish an intelligent triage system that can optimize the clinical decision-making at the time of a global pandemic. The clinical presentation and patients' characteristics are usually utilized to identify those patients who need more critical care. However, the clinical evidence shows an unmet need to determine more accurate and optimal clinical biomarkers to triage patients under a condition like the COVID-19 crisis. Here we have presented a machine learning approach to find a group of clinical indicators from the blood tests of a set of COVID-19 patients that are predictive of poor prognosis and morbidity. Our approach consists of two interconnected schemes: Feature Selection and Prognosis Classification. The former is based on different Matrix Factorization (MF)-based methods, and the latter is performed using Random Forest algorithm. Our model reveals that Arterial Blood Gas (ABG) O2 Saturation and C-Reactive Protein (CRP) are the most important clinical biomarkers determining the poor prognosis in these patients. Our approach paves the path of building quantitative and optimized clinical management systems for COVID-19 and similar diseases. Graphical abstract: Image 1 Highlights: Subspace learning, matrix factorization, manifold learning, and correlation analysis are powerful tools to develop feature selection methods. Novel feature selection based on the matrix factorization can be successfully applied for the two categories biomarkers and clinical data. High-dimensionality reduction of blood biomarker space in this study shows the blood biomarkers for in poor prognosis in COVID-19.